ANALISIS HUKUM ADMINISTRASI NEGARA DALAM MENGATASI PERMASALAHAN SAMPAH DI KOTA MATARAM NTB - Agung Setiawan; Riska Ari Amalia (Bajang Institute, 2025)
Case Study Research: The purpose of this research is to analyze the State Administrative Law Strategy in Addressing Waste Problems in Mataram City, NTB. To obtain excellent research results, the method used in this research is a normative juridical research method. Law is described as what is written in legislation (law in books) or law is conceptualized as rules or norms that serve as benchmarks for human behavior that are considered appropriate. This normative legal research consists of primary and secondary legal materials, namely research that refers to the norms contained in legislation. To facilitate this research, a statute approach method was used. The results of the research are that regulatory policies related to waste have not fully resolved the waste problem in NTB. Waste management infrastructure in NTB is not optimal, so a good State Administrative Law Strategy is needed to address the waste problem in Mataram City, NTB. In addition, a collaborative participatory approach is needed between the local government and all levels of society committed to resolving the waste problem in NTB.